2016
DOI: 10.1590/1982-0224-20160021
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of two coexisting invasive sailfin catfishes (Siluriformes: Loricariidae) in a tropical region of Mexico

Abstract: Currently many species of Amazon sailfin catfishes (Loricariidae) have been introduced to wild environments outside their native range. There is, however, little knowledge about their role as vectors of parasites that can infect native fish or even humans through its consumption. The aim of the present study was to determine the parasitic fauna of the invasive sailfin catfish species Pterygoplichthys pardalis (leopard pleco) and P. disjunctivus (vermiculated pleco) from freshwater systems in the southeast of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(35 reference statements)
0
7
0
3
Order By: Relevance
“…It is important to mention that most human-parasite disease transmission is mainly associated with the consumption of raw seafood dishes i.e., sushi, sashimi, ceviche (Kuchta et al, 2005ab). Most of the species potentially pathogenic to human are pathogenic mostly in larval stage, i.e., L1 and L3 in nematodes, plerocercoid in cestodes and metacercariae in digenan trematodes (Rodriguez-Santiago et al, 2016). Consequently, the ingestion of bivalves such as oysters as a source of raw food may have a health risk factor and should be explored further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that most human-parasite disease transmission is mainly associated with the consumption of raw seafood dishes i.e., sushi, sashimi, ceviche (Kuchta et al, 2005ab). Most of the species potentially pathogenic to human are pathogenic mostly in larval stage, i.e., L1 and L3 in nematodes, plerocercoid in cestodes and metacercariae in digenan trematodes (Rodriguez-Santiago et al, 2016). Consequently, the ingestion of bivalves such as oysters as a source of raw food may have a health risk factor and should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the host-parasite Biomphalaria-Schistosoma mansoni is responsible for human schistosomiasis (Hung et al, 2013; Hotez et al, 2014; Keiser & Utzinger, 2009). Metacercarie Clinostomum complanatum has been mainly found in fish P. pardalis in the southwest of Mexico (Rodriguez-Santiago et al, 2016), and members of this species have been found attached to the human larynx and pharynx after eating raw seafood (Witenberg, 1944; García et al, 2007; Park et al, 2009). Thus, the consumption of raw fish and bivalves such as oysters potentially poses a health risk and should be explored further, motivating this study of parasites in the much understudied mollusk: the pleasure oyster Crassostrea corteziensis (Hertlein, 1951).…”
Section: Introductionmentioning
confidence: 99%
“…Se han reportado parásitos en diferentes especies de plecos (Sanz, 2010;Rodríguez-Santiago et al 2016), pueden transferir e introducir patógenos, parásitos y enfermedades ajenas a las especies nativas, poniendo en riesgo la salud de las poblaciones locales (Martinez, 2007).…”
Section: )unclassified
“…de importancia internacional (conocido como Proyecto Humedales), con el auspicio del Fondo para el Medio Ambiente Mundial (GEF), administrado por el Programa de las Naciones Unidas para el Desarrollo (PNUD) e implementado por el Sistema Nacional de Áreas de Conservación (SINAC) (Proyecto Humedales, 2017). Lo cual permitió el intercambio disciplinario de la biología, en conjunto con la economía, para la realización del análisis en cuestión.…”
Section: Introductionunclassified
“…Looss, 1899 en el manto, y glándula digestiva del ostión C. corteziensis en las costas de Sinaloa. En el Golfo de México, se ha registrado la presencia de metacercarias como Clinostomum complanatum (Rudolphi, 1814) que se ha encontrado principalmente en peces P. pardalis en el suroeste de México (Rodríguez-Santiago et al, 2016) este pescado se utiliza en la elaboración de ceviche, platillo gastronómico de comida típica en las costas. Los miembros de esta especie de parásito se han encontrado unidos a la laringe y faringe humana después de comer mariscos crudos desde su primer registro (Chung et al, 1995) hasta la actualidad (Hara et al, 2014;Lee et al, 2017;Hyun et al, 2018 (Ten et al, 2019).…”
Section: Introductionunclassified